Energy Based Evaluation of Routing Protocol for MANETs - Kishore, Nand; Singh, Sukhvir; Dhir, Renu (International Journal of Computer Sciences and Engineering, 2014)
A Mobile ad hoc network is a collection of mobile nodes connected through wireless links forming an temporary network without fixed topology, centralized access point, infrastructure. In such a network, each node can act as a router and host simultaneously, it can move out or join in the network freely as required. Various routing protocols have been discussed so far in this paper a brief comparison of two reactive protocols DSR and AODV along with proactive protocol DSDV will be done. Detail study of the network performance such as throughput, packet delivery ratio, energy consumption. The simulations are carried out using NS-2 simulator. The results presented specify the importance in careful evaluation and implementation of routing protocols in an ad hoc environment.